2017
DOI: 10.1094/pdis-01-17-0110-re
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Novel Phylotype ofPseudomonas syringaeCausing Bacterial Leaf Blight of Cantaloupe in China

Abstract: Bacterial leaf blight (BLB) has caused severe yield losses in cantaloupe (Cucumis melo L.) in the major melon-growing regions of China since the beginning of the twentieth century. Historically, Pseudomonas syringae pv. lachrymans was considered to be the causal agent of BLB of cantaloupe and angular leaf spot of cucumber. In the process of characterizing bacteria isolated from cantaloupe, we observed that putative P. syringae pv. lachrymans yielded negative results in P. syringae pv. lachrymans-specific PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…lachrymans. However, recent research implicates multiple P. syringae pathovars, including pathovars syringae and aptata (Langston Jr. et al 2003;Newberry et al 2018;Tian et al 2017), as well as other Pseudomonas species, including P. alliivorans, P. capsici, P. cichorii, and P. viridiflava (Fullem et al 2024;Newberry et al 2016;Obradovic and Arsenijevic 2002), as causal agents of the disease. This publication is intended to provide information on the disease bacterial leaf spot of cucurbits, its epidemiology, and management to cucurbit growers in the southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…lachrymans. However, recent research implicates multiple P. syringae pathovars, including pathovars syringae and aptata (Langston Jr. et al 2003;Newberry et al 2018;Tian et al 2017), as well as other Pseudomonas species, including P. alliivorans, P. capsici, P. cichorii, and P. viridiflava (Fullem et al 2024;Newberry et al 2016;Obradovic and Arsenijevic 2002), as causal agents of the disease. This publication is intended to provide information on the disease bacterial leaf spot of cucurbits, its epidemiology, and management to cucurbit growers in the southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it can be found in diverse agricultural environments and is one of the most studied bacterial plant pathogens worldwide (Yan et al, 2008). In recent years, some researches have reported that P. syringae can cause various plant diseases, such as bleeding canker of Aesculus hippocastanum (Webber et al, 2010), bacterial canker of Actinidia chinensis Planch (Everett et al, 2011), bacterial brown spot of Avena storigosa Schereb (Ishiyama et al, 2013), leaf spots of Cucurbita pepo (Balaz et al, 2014), leaf blight of Cucumis melo (Tian et al, 2017), bacterial blister bark of Malus pumila (Gasic et al, 2018), halo blight of Avena sativa (Persson and Sletten, 2001), leaf streak and black chaff of Triticum aestivum (Amanifar, 2019), etc. However, some studies found that P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%